Cumulative Motor Index: An Index to Study Progression of Amyotrophic Lateral Sclerosis. Issue 1 (February 2015) - Nandedkar, Sanjeev D.; Barkhaus, Paul E.; Stålberg, Erik V.
Abstract : Purpose: To study disease progression in patients with amyotrophic lateral sclerosis (ALS), we have developed the "cumulative motor index (CMI)" using the compound muscle action potential amplitude recorded in multiple upper and lower limb muscles. Methods: To study its reproducibility, CMI was measured by 2 operators in 10 healthy subjects on 2 occasions. In 15 patients with ALS, CMI and ALS functional rating score (revised) were measured at 3- to 6-month interval for 12 months or longer. Results: The CMI had good reproducibility in healthy subjects. In one patient with ALS, CMI and ALS functional rating score (revised) remained relatively unchanged. In all remaining 14 patients with disease progression, CMI decreased in a relatively monotonic manner. At 1 year after baseline study, CMI was reduced more than ALS functional rating score (revised) in 10 patients. CMI measurements were possible for longer time period, than analysis from a single distal muscle recording. Conclusions: The CMI can be measured using standard equipment and software available in most electrodiagnostic laboratories. This may be a simple measurement that can be used for clinical studies of ALS progression over longer time periods.